Hardy–Sobolev spaces associated with Hermite expansions and interpolation. (July 2017) - Huang, Jizheng
Abstract: Let A = − Δ + | x | 2 be a Hermite operator, where Δ is the Laplacian on R d . In this paper, we first define the Hardy–Sobolev spaces associated with Hermite expansions, then we give the atomic decomposition and the real interpolation with Sobolev spaces. As an application, we consider the endpoint version of the div–curl theorem for the Hermite operator.